Komparasi Struktur Imaji dalam Lirik Lagu "Kokoro No Tomo" dengan Versi Remake oleh Grup Musik Zivilia - Darmawan, Ricky; Kistanto, Nurdien H; Suryadi, M (IZUMI, 2023)
Image is a word or a word arrangement that has the effect of clarifying or concretizing what the poet has stated. Images in literary works include many kinds of things related to human senses. This study compares and equates the emphasis on figurative language style in the lyrics of songs with two language translation versions of the same name, Kokoro no Tomo which was set to music by Mayumi Itsuwa in 1980 and popularized in the world. Translated in Indonesian with the title Kokoro no Tomo by the music group Zivilia. The method used by the author in the research is a qualitative method, focusing on comparing the images in the lyrics of the song. The results of visual exploration of similarities and differences in the lyrics of the two songs include (1) sensational images, (2) tactile images, and (3) visual images. an illustration that both versions provide an equivalent statement with sentences from the Japanese and Indonesian versions. With the difference in the use of images, the lyrics of the two songs have adjusted the content to suit the musical needs of the people, especially in this case, the people of Indonesia gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor